A Sustaining Operational Performance during Command Training: The Interplay of HR Policy, Leadership Sense-making, and Unit Resilience in a Police Context: The Interplay of HR Policy, Leadership Sense-making, and Unit Resilience in a Police Context - Wibowo, Hendro; Rini Rahmawati; Meiske Claudia (CITACONOMIA : Economic and Business Studies, 2026)
Career-level training like SESPIM is critical for leadership development in police forces but creates a unique "hybrid work" challenge. For a full semester, officers are physically and mentally detached from their home units ("remote"), creating a performance vacuum in their absence. This study investigates how police organizations manage this inevitable disruption. Existing literature on police training focuses on individual learning outcomes, neglecting the systemic impact on the sending units and the organizational mechanisms that sustain performance during this period. This conceptual paper employs an integrative review, applying a multi-level organizational behavior lens to the specific context of police professional development. We propose that macro-level HR policies (e.g., interim position management, performance accountability protocols) set the stage. However, their effectiveness hinges on the meso-level sensemaking of both the training officer (maintaining virtual influence) and the acting commander at headquarters. This leadership dynamic directly impacts the micro-level resilience processes (shared leadership, procedural adaptation, maintained morale) of the remaining (left-behind) unit, determining its ability to sustain operational performance. The article provides a novel framework for understanding human resource management in law enforcement, offering strategic insights for police leadership on how to strategically plan for and mitigate the performance risks associated with essential long-term training.